The effect of climatic conditions on occupants' thermal comfort in naturally ventilated nursing homes. (15th April 2022) - Baquero Larriva, María Teresa; Mendes, Ana Sofía; Forcada, Nuria
Abstract: Climatic conditions influence thermal comfort. However, the effect of climatic conditions on occupants' thermal comfort in naturally ventilated nursing homes has not been analysed. This paper reports on a study to analyse the climate influence on the thermal perceptions of residents (elderly people) and non-residents (caregivers and therapists) from 18 nursing homes in three climatic zones: Csa-m (Mediterranean climate); Csa-c (continental Mediterranean climate) and Csb (oceanic Mediterranean climate). A mixed methodology was used including environmental measurements and on-site surveys during naturally ventilated seasons. A total of 2690 surveys were collected: 550 in Csb climate nursing homes, 1252 in Csa-m and 888 in Csa-c. The results highlighted that nursing homes' occupants (elderly people and other adults) from the different climates perceived thermal comfort differently within naturally ventilated conditions. Outdoor temperature and outdoor humidity were found to influence indoor thermal sensation in the climates. Therefore, outdoor relative humidity should be considered when thermal comfort standards are developed, or thermal comfort is analysed. Neutral temperature for elderly people was found to be dependent on climate. These findings carry significant implications for regulatory bodies to develop guidelines for the design and operation of nursing homes in different climates. Highlights: Elderly from the different climates has different thermal perception. Apart from the temperature, outdoor humidity also influences indoor thermal comfort. Neutral temperature for elderly depends on the climate. High indoor humidity implies higher heat sensation. The real elderly thermal sensitivity was lower than PMV prediction model.